Effect of Cypermethrin on Hematological and Histological Parameters in Male Albino Mice - Jaafer, Noor S.; Rabee, Adel M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The study investigated the behavioral, hematological, and histological changes of sub-lethal toxicity of Cypermethrin, a synthetic parathyroid insecticide, in male albino mice. The mice were divided into three groups, with the control group remaining untreated and the other groups treated with different doses. The behavioral effects produced mild to moderate toxic symptoms. The lower dose produced very mild toxicities characterized by intermittent diarrhea and decreased feed intake, whereas the higher dose displayed mild to moderate toxicities with diarrhea, decreased feed intake, loss of body weight, dyspnea, ataxia, eye discharge, and salivation. Hematological parameters such as packed cell volume (PCV), hemoglobin concentration (HB), white blood count (WBC), and red blood count (RBC) were evaluated. Hematological parameters such as PCV, HB, RBC, and WBC showed a dose-dependent reduction. At the same time, microscopically, cypermethrin produced neuronal degeneration and depletion of glycoprotein with accumulation of cholesterol in which the hepto-cells appear as a plant cell, and disorganization of hepatic laminae, dilation of sinusoids, and necrosis of hepatocytes in the liver. Section of kidney displayed hemorrhage and sloughing of renal epithelial cells in the convoluted tubules, shrinkage of glomeruli, and necrosis of renal tubules. The above observations clearly demonstrate that hematological parameters such as packed cell volume, hemoglobin concentration, total erythrocyte count, and total leukocyte count showed a dose-dependent reduction. There were relative variations in results in CYP-intoxicated groups.  The changes in the blood picture indicate the toxic actions of CYP on the hematopoietic system. Nevertheless, we believe that the studies addressing the comparison of histopathological and behavioral effects would be very helpful in the evaluation of pyrethroid insecticides. In addition to the overall results of this study, which clearly demonstrate that oral administration of the (CYP) leads to histopathological changes in the liver, as well as the kidneys, in mammals and environmental systems